Pomegranate Extract Does Not Inhibit Sodium Glucose co-Transporter 2 Protein in Vero Cells - Mila Ulfia; Dono Indarto; Amelya Augusthina Ayu Sari; Yuliana Heri Suselo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Backgrounds: Mutation of SLC5A2 gene which encodes sodium glucose co-transporter2 (SGLT2) protein enhances glucose reabsorption on the kidney tubule in some patients with type 2 diabetes (DMT2). Dapagliflozine an oral antidiabetic drug, inhibits SGLT2 activity. Ellagic acid is able to inhibit SGLT2 protein in silico and highly found in pomegranate fruits. The aim of this study was to investigate the effect of pomegranate extracts on glucose levels in a model cell of African green monkey (Vero cell line). Methods: This study was an experimental laboratory with posttest only control group design. 1 x 106 Vero cells perwell were used in five experimental groups: negative control 1 (KKn1), KKn with 20% glucose (KKn2), positive control with dapagliflozine (KKp), ethanol and diethyl ether extract of pomegranate peel (KEDA), methanol extract of pomegranate seeds (BMA). Vero cells were then treated with 125 ppm pomegranate extracts (KEDA and BMA) and incubated for 24 hours. Cell morphology was observed under an inverted microscope with 100 x magnification. Glucose levels in Vero cells were measured using spectrophotometer. Collected data was analyzed descriptively. Result: Morphology of Vero cells was oval, soliter and centered nucleus and did not change during incubation with pomegranate extracts. Glucose levels in Vero cells treated with BMA (28.5 mg/dL) and KEDA (29 mg/dL) were higher than glucose levels in control groups KKp, KKn1, and KKn2 (2.5, 6.5 and 8 mg/dL respectively). Conclusion; Pomegranate extracts do not inhibit SGLT2 protein and increase glucose levels in Vero cells. Purification of pomegranate extracts is required for further investigation of the capability of ellagic acid inhibiting SGLT2 protein. Keywords: Ellagic acid, glucose level, pomegranate, SGLT2, type 2 diabetes.